2013
DOI: 10.1111/tran.12025
|View full text |Cite
|
Sign up to set email alerts
|

Making country good: stewardship and environmental change in central Australian pastoral culture

Abstract: Rural stewardship has been a focus of much natural resource management policy in Australia and elsewhere. Despite landowners professing stewardship, some researchers have cast doubt on the utility of the concept due to its vagueness and difficulties of associating attitudes with behaviour. In contrast I argue that stewardship should remain an important concept for understanding rural cultures, landholder practices and the politics of land. Stewardship, however, needs to be understood as emergent, as a ‘dwelt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…For example, well-designed collaborative landscape-scale schemes were found to be more beneficial than farm-scale schemes for a small but significant number of key farmland species and ecosystem services, although unlikely to harm species operating at smaller scales (McKenzie et al 2013). Landscape stewardship is also important for understanding cultures, landholder practices, and the politics of land (Gill 2014). It has been shown that landscape stewardship is closely related to place attachment, thus affecting people's attitudes toward conservation and planning (Lokocz et al 2011).…”
Section: Landscape Stewardshipmentioning
confidence: 99%
“…For example, well-designed collaborative landscape-scale schemes were found to be more beneficial than farm-scale schemes for a small but significant number of key farmland species and ecosystem services, although unlikely to harm species operating at smaller scales (McKenzie et al 2013). Landscape stewardship is also important for understanding cultures, landholder practices, and the politics of land (Gill 2014). It has been shown that landscape stewardship is closely related to place attachment, thus affecting people's attitudes toward conservation and planning (Lokocz et al 2011).…”
Section: Landscape Stewardshipmentioning
confidence: 99%
“…), which may explain the lack of meaningful difference between many incentivized and nonincentivized proenvironmental actions we examined. As noted by Gill (), linking specific events, activities, or values with overall sense of stewardship can be somewhat fraught.…”
Section: Discussionmentioning
confidence: 99%
“…That landscapes of private property and production predominate in the post-colonial era suggests uniformity in ideologies of nature and land stewardship. Ideas about rural land-use are heterogeneous and evolving, however (Gill, 2014). In recent decades, rural to exurban transitions in Australia are diversifying attitudes and values among rural residents, creating a complex "management mosaic" (Epanchin-Niell et al, Gosnell, Haggerty, & Travis, 2006) and leading to both intended and unintended socioecological consequences (Abrams, Gosnell, Gill, & Klepeis, 2012;Gill, Klepeis, & Chisholm, 2010;Mendham, Curtis, & Millar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notions of land stewardship evolve (Cooke & Lane, 2015;Gill, 2014), and community discourse in amenity landscapes create and re-craft knowledge about socio-ecological systems (Larsen & Hutton, 2012). Emerging amenity landscapes experience dynamic change.…”
mentioning
confidence: 99%